The Synthesis and Characterization of A New Composite Material Ca-Mg-NH₄-PO₄ Dolomite-Based for Effective Multinutrient Fertilizer in Plant Growth - Noni Aulia; Vica Brilliany Sanjaya; Ketut Sumada; Lilik Suprianti (Jurnal Kimia Sains dan Aplikasi, 2024)
The rapid expansion of Indonesia's agricultural sector has led to a surge in fertilizer demand. Dolomite lime shows potential as a promising alternative material to enhance fertilizer quality. This study aims to synthesize and characterize a Ca-Mg-NH4-PO4 composite using dolomite as a precursor through precipitation. The synthesis was successfully achieved through several stages, beginning with dolomite preparation, dissolution in 5N phosphoric acid, and subsequent precipitation with ammonium hydroxide at pH 8, 30°C, with a stirring speed of 450 rpm. The resulting composite was analyzed using various analytical techniques to evaluate its structural, morphological, and elemental compositions. X-Ray Diffraction (XRD) results indicated the formation of struvite crystals at positions 2θ = 20.828°, 30.539°, 33.234°, brushite crystals at position 2θ = 11.650°, and impurity compounds that appeared during the synthesis process. Impurities affecting crystal purity were detected but could be minimized through washing. Scanning Electron Microscopy (SEM) analysis revealed a monoclinic crystal morphology with particle sizes ranging from 4.32 μm to 579 nm. X-Ray Fluorescence (XRF) and Energy Dispersive X-Ray (EDX) analysis verified the presence of Ca, Mg, NH₄, and PO₄ components in the composite. Fourier-Transform Infrared Spectroscopy (FTIR) analysis showed that the composite has P-O-C functional groups at 949 cm⁻¹, 972 cm⁻¹, and 1027 cm⁻¹, and N-H functional groups at 1466 cm⁻¹. Overall, this Ca-Mg-NH₄-PO₄ composite derived from dolomite demonstrates promising characteristics as a multi-nutrient fertilizer, offering a high-quality option to support sustainable agricultural practices.